PENDAMPINGAN IMPLEMENTASI PRINSIP KEADILAN DAN MASLAHAT DALAM SKEMA POTONGAN PELUNASAN DINI PEMBIAYAAN MURABAHAH DI PONDOK PESANTREN ARRAHMAN CIDADAP - Syarif Hidayatullah (DEVELOPMENT: Journal of Community Engagement, 2023)
This research is a comprehensive report on a community service program conducted at the Arrahman Cidadap Islamic Boarding School, Sukabumi. The primary focus of this study is an in-depth analysis and assistance in the implementation of the National Sharia Board-Indonesian Council of Ulama (DSN-MUI) Fatwa Number 153/DSN-MUI/VI/2022 concerning the Early Settlement of Murabahah Financing Debt, which revises the old paradigm of Fatwa Number 23/DSN-MUI/III/2002. This research is motivated by academic and practical concerns regarding the low literacy of the boarding school's financial managers regarding the legal shift from a "voluntary" nature (jawaz) to "mandatory" (wujub) in providing discounts (muqassah) for customers who settle their debts early. Using the Participatory Action Research (PAR) method, this research involved the active participation of the boarding school's cooperative administrators in three cycles: problem mapping, educational action, and system institutionalization. The research findings indicate that prior to the intervention, murabahah practices at the Arrahman Cidadap Boarding School tended to ignore the principle of distributive justice, where the profit margin was still taken in full even though the financing duration was significantly reduced due to early settlement. Through a dialogical PAR approach, the community service team successfully reconstructed the understanding of the asatidz and financial managers that muqassah is not merely a reduction in profit, but a theological mandate to uphold the principles of al-'adalah (justice) and al-maslahah (public interest) to avoid ghubn (unilateral loss) and consuming wealth unjustly. The final result of this community service is the establishment of a new Standard Operating Procedure (SOP) that integrates a proportional calculation formula in accelerated settlements, which has been proven to increase the trust of the students' guardians and the institution's liquidity. This report recommends the need for massive socialization of the latest DSN-MUI fatwas to the economic bases of the ummah in rural areas to prevent a gap between sharia idealism and field reality.